Outlook of Covid-19 Curing through Structural and Electronic Properties of Natural Drugs - (:unkn) unknown (AMG Transcend Association, 2022)
Humans and multiple species of animals must be infected by coronaviruses (positive-stranded RNA viruses) through enteric, respiratory, and central nervous system sickness with attractive targets for designing anti- Covid-19 conjunction. In this work, it has been investigated the compounds of luteolin-7- glucoside, curcumin, epicatechin-gallate, allicin, and zingerol as probable anti-pandemic Covid-19 receptors derived from medicinal plants. Anti-Covid-19 through the hydrogen bonding using the physicochemical features consisting of thermodynamic parameters, nuclear magnetic resonance analysis, and IR characteristics, of luteolin-7- glucoside, curcumin, epicatechin-gallate, allicin, and zingerol compounds binded to the fragment of Tyrosine-Methionine-Histidine as the selective area of the Covid-19, IR frequency and intensity of various normal modes of these structures have been estimated. The theoretical calculations were accomplished at different steps of theory to achieve the more accurate equilibrium geometrical consequences, and IR spectral analysis for each of the complex drugs of O-terminal or N-terminal auto-cleavage substrate were approved to clear the structural flexibility and substrate attaching of seven medicinal plants bonded to the active site of Covid-19 molecule. Comparing these compounds with two configurations prepares a new outlook for the design of substrate-based anti-targeting of Covid-19. This indicates a feasible model for designing a wide spectrum of anti-Covid-19 drugs. The compounds-based energy minimization of these materials has resulted in two more effectual lead compounds, N and O atoms, forming the hydrogen bonding (H-bonding) with potent anti- Covid-19. Finally, two medicinal ingredients of allicin, curcumin, luteolin-7- glucoside, and zingerol bonded to TMH have been directed to a Monte Carlo (MC) simulation and UV-Visible for estimating the absorbance of luteolin-7- glucoside, and epicatechin-gallate.
Keywords: 3. Good health